If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (50x + -8y) + (32x + 37y) = 0 Remove parenthesis around (50x + -8y) 50x + -8y + (32x + 37y) = 0 Remove parenthesis around (32x + 37y) 50x + -8y + 32x + 37y = 0 Reorder the terms: 50x + 32x + -8y + 37y = 0 Combine like terms: 50x + 32x = 82x 82x + -8y + 37y = 0 Combine like terms: -8y + 37y = 29y 82x + 29y = 0 Solving 82x + 29y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29y' to each side of the equation. 82x + 29y + -29y = 0 + -29y Combine like terms: 29y + -29y = 0 82x + 0 = 0 + -29y 82x = 0 + -29y Remove the zero: 82x = -29y Divide each side by '82'. x = -0.3536585366y Simplifying x = -0.3536585366y
| 24+x=-18 | | -3x^2-12x+1=0 | | 28=w(2w-1) | | (x-2)(x+4)=14 | | x^2+x-36= | | 12c+5=c+31 | | 35x+-14=36x+-6 | | -18=x+20 | | 36x-14=36x-6 | | -22=11(2c-8) | | |-14|= | | (22-18)x(3+8)= | | x-24=6 | | 2(2)+3(4a)-4(3+3a)+3=0 | | 3y-24-6y+37= | | 4d^2-4d-80=0 | | x-8.8=-6.8 | | 2=2m+2+6m | | (q*q*q)-6(q*q)-21600=0 | | 12/3x5-16 | | 10-x/4x | | 6(2x+2)+15= | | -2/-1 | | 0=x^4-6x^3-x^2+20x | | 2.6-5.1=6.6 | | 3x/4-1/3(3x-6)=5/2(6-x/2) | | 6(2x^2-9x-18)=0 | | 8x/3-2x-6 | | 11x^3-x+9=x^3+45x^2+x | | 683+2x=53 | | 18-(2m+5)=4+2m-15 | | 6(4x+15)+13x-12= |